CHARACTER ANALYSIS OF MAIN CHARACTER IN SONS AND LOVERS WRITTEN BY D.H. LAWRENCE - Erika Dwi Koestanti (LPPM Universitas Bina Sarana Informatika, 2016)
Novel is one of human literature creation. Novel consist of five intrinsic elements are theme, character, setting, plot and point of view. Character is someone who acts appears or referred to as playing a park in literary work. Main Character is who are typically characterized fully. Characters make the novel more interesting to read by the reader. The writer chooses the novel that is one of elements of literature, because according to the writer by reading a novel can be developed English skill to the readers. Here, the writer chose character analysis of main character in Sons and Lovers novel written by D.H. Lawrence as her analyses to finish the thesis so that the writer can know that there are six characters in this novel are Flat Character, Round Character, Static Character, Dynamic Character, Protagonist and Antagonist. The writer analyzed the character of Paul Morel and Gestured Morel in Novel Sons and Lovers is written by D.H. Lawrence because this novel is very interesting. The characters in the novel contains the biography of the life of the author that the characters replaced by the name of the author DH Lawrence and the story about the Oedipus complex.